2009
DOI: 10.1002/ana.21594
|View full text |Cite
|
Sign up to set email alerts
|

Declined neural efficiency in cognitively stable human immunodeficiency virus patients

Abstract: Objective-To determine whether brain activation changes in clinically and neurocognitively normal human immunodeficiency virus (HIV)-infected and in HIV-seronegative control (SN) participants over a 1-year period.Methods-Functional magnetic resonance imaging (fMRI) was performed in 32 SN and 31 HIV patients (all with stable combination antiretroviral treatment) at baseline and after 1 year. Each participant performed a set of visual attention tasks with increasing attentional load (from tracking two, three, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
91
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 44 publications
15
91
0
Order By: Relevance
“…At baseline, HIV participants showed a reorganized neural network compared to SN participants even on the relatively simple 1‐back task, with greater activation in the medial and lateral frontal regions, but lesser activation in brainstem and bilateral cingulate gyri, which are consistent with previous studies of WM and sustained attention tasks in HIV participants 20, 22, 23, 41. Similarly, on the 2‐back task, the greater activation in bilateral medial frontal regions and the right precentral gyrus is also consistent with greater usage of the reserve attention network, or increased attentional modulation for this more‐difficult task in HIV patients 21, 24…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…At baseline, HIV participants showed a reorganized neural network compared to SN participants even on the relatively simple 1‐back task, with greater activation in the medial and lateral frontal regions, but lesser activation in brainstem and bilateral cingulate gyri, which are consistent with previous studies of WM and sustained attention tasks in HIV participants 20, 22, 23, 41. Similarly, on the 2‐back task, the greater activation in bilateral medial frontal regions and the right precentral gyrus is also consistent with greater usage of the reserve attention network, or increased attentional modulation for this more‐difficult task in HIV patients 21, 24…”
Section: Discussionsupporting
confidence: 87%
“…However, in that follow‐up study, HIV neuroasymptomatic participants showed increased, rather than decreased, BOLD signals, suggesting declined efficiency with no practice effects 23. Future fMRI studies to evaluate brain activation after nonadaptive WMT is needed to delineate WMT from practice effects.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations